Engineered mesenchymal stem cells as treatment for cancers: opportunities, clinical applications and challenges - Shamsul Kamal, Aishah Amirah; Fakiruddin, Kamal Shaik; Abubakar Bobbo, Khadijat; King, Hwa Ling; Vidyadaran, Sharmili; Abdullah, Syahril (Penerbit Universiti Sains Malaysia, 2024)
The insufficient and unspecific target of classical chemotherapies often leads to therapy resistance and cancer recurrence. Over the past decades, discoveries about mesenchymal stem cell (MSC) biology have provided new potential approaches to improve cancer therapy. Researchers have utilised the multipotent, regenerative and immunosuppressive qualities of MSCs and tropisms towards inflammatory, hypoxic and malignant sites in various therapeutic applications. Although MSC-based therapies have generally been demonstrated safe, their effectiveness remains limited when these cells are used alone. However, through genetic engineering, researchers have proven that MSCs can be modified to have specialised delivery roles to increase their therapeutic efficacy in cancer treatment. They can be made to overexpress therapeutic proteins through viral or non-viral genetic modification, which enhances their innate properties. Nevertheless, these engineering strategies must be optimised to increase therapeutic efficacy and targeting effectiveness while minimising any loss of MSC function. This review underscores the cutting-edge methods for engineering MSCs, discusses their promise and the difficulties in translating them into clinical settings, and offers some prospective suggestions for the future on achieving their full therapeutic potential.